Molecular phylogenetics of the orchid genus Spathoglottis (Orchidaceae: Collabieae) in Peninsular Malaysia and Borneo - Nordin, Farah Alia; Saibeh, Kartini; Go, Rusea; Abu Mangsor, Khairul Nasirudin; Othman, Ahmad Sofiman (Multidisciplinary Digital Publishing Institute, 2022)
Phylogenetic relationships of the orchid genus Spathoglottis (Orchidaceae: Collabieae) in Peninsular Malaysia and Borneo were inferred using the internal transcribed spacer of a nuclear ribosomal DNA (nrITS), a plastid gene maturaseK (matK) and the plastid region trnL-F. Eleven species and three infraspecific taxa of Spathoglottis were examined, with two outgroup species, were included in the phylogenetic analysis. The combined plastid and nuclear data revealed Spathoglottis as monophyletic. From the maximum likelihood, maximum parsimony and Bayesian analyses, Spathoglottis is divided into four major groups which are, (1) the Dwarf Purple Spathoglottis, (2) the Dwarf Yellow Spathoglottis, (3) the Large Purple Spathoglottis, and (4) the Large Yellow Spathoglottis. The split in the Dwarf and Large Spathoglottis groups might reflect an early differentiation of plant size, flower colours and flower size. Phylogeny reconstruction of the orchid genus Spathoglottis also exhibited strong support towards the taxonomic delimitation of the two mostly debated taxa in the genus, S. aurea and S. microchilina.